The Effect of SQ3R (Survey, Question, Read, Recite, and Review) combined with Numbered Head Together on Students' ReadingComprehension at Eight Grade Students of SMP Saraswati Seririt in the Academic year 2014/2015 - ., Ni Komang Fina Sasmita Sari; ., Dr.Sudirman, M.L.S; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menyelidiki apakah ada atau tidak ada perbedaan yang signifikan dalam pemahaman membaca antara siswa yang diajar dengan menggunakan SQ3R (Survey, Question, Read, Recite, and Review) dikombinasikan dengan Numbered Head Together Strategi dan mereka yang diajarkan dengan menggunakan Teknik Konvensional. Desain Post-Test untuk Kontrol Grup yang acak digunakan dalam penelitian ini. Populasi dalam penelitian ini adalah siswa kelas VIII SMP Saraswati Seririt. Mereka adalah kelas VIIIB sebagai kelompok eksperimen yang diajarkan dengan SQ3R (Survey, Question, Read, Recite dan Review) dikombinasikan dengan Numbered Head Together dan kelas VIIIA sebagai kelompok kontrol yang diajarkan dengan Teknik Konvensional. Instrumen yang digunakan adalah scenario pengajaran dan tes pemahaman membaca. Data yang diperoleh dalam penelitian ini dianalisis baik secara deskriptif dan inferensial. Hasil analisis menunjukkan bahwa siswa yang diajar dengan Strategi SQ3R (Survey, Question, Read, Recite, and Review) dikombinasikan dengan Numbered Head Together lebih baik daripada mereka yang diajar dengan Teknik Konvensional. Ini dibuktikan dari nilai rata-rata dari kelompok eksperimen yaitu 82,23, sedangkan kelompok kontrol adalah 75,61. Kata Kunci : Pemahaman Membaca, SQ3R (Survey, Question, Read, Recite, and Review) dikombinasikan dengan Numbered Heads Together This study aimed at investigating whether or not there was a significant difference in reading comprehension between the students who were taught by using SQ3R combined with Numbered Head Together and those who were taught by using conventional strategy. The research design of this study was Post-test Only Control Group Design. The population was the eighth grade students of SMP SaraswatiSeririt. Cluster Random Sampling was assigned to select the sample of the study.Class VIII.B was assigned as the experimental group which was taught by using SQ3R combined with Numbered Head Together and class VIII.A as the control group which was taught by using conventional strategy.The result of the data analysis showed that students in experimental group performed better reading than students in control group. It was proven by the result of descriptive statistics that showed the mean score the experimental group was 82.23, while the mean score of control group was 75.61. The result of the t-test also showed that the value of the tobs was higher than thetcv. keyword : Reading Comprehension, SQ3R (Survey, Question, Read, Recite and Review combined with Numbered Heads Together